TINGKAT KERUSAKAN BERDASARKAN ZONASI HUTAN MANGROVE DI DESA NIPAH PANJANG KECAMATAN BATU AMPAR KABUPATEN KUBU RAYA - Rifanjani, Slamet; Effendi, Fellin Shafira; Wulandari, Reine Suci (Universitas Tanjungpura, 2024)
Overexploitation threatens the existence of mangrove forests which results in a decrease in the quality of the mangrove ecosystem, especially in Nipah Panjang Village. Damage was caused by logging activities for building construction and firewood. The destruction of mangrove forests results in the loss of biodiversity and its role, especially mangrove vegetation. The purpose of this study was to obtain a value for the level of damage to mangrove forest vegetation, examine the composition and structure of the vegetation based on the zoning and level of damage to mangrove forests in Nipah Panjang Village, Batu Ampar District, Kubu Raya Regency. The method used is a survey using a combination of lines and checkered lines. The forest area is located at the mouth of the river where there is a mixture of fresh water and salt water (brackish) with a salinity of 16